Evaluating the impact of NSAIDs and exercise therapy versus sole exercise therapy on joint mobility, pain levels, grip strength, and muscle activity in lateral epicondylitis patients - Junaid Ahmad Parrey; Mohd Arshad Bari; Abdul Qayyum Khan; Arish Ajhar; Shivani Singh (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Aim and Background: Lateral epicondylitis (LE), or tennis elbow, is a common musculoskeletal disorder causing pain, reduced grip strength, and limited wrist range of motion (ROM). This study aimed to compare the effects of NSAIDs combined with exercise therapy versus exercise therapy alone on wrist ROM, pain, grip strength, and electromyographic (EMG) activity of the extensor digitorum communis (EDC) muscle in LE patients. Material and Method: Eighty participants were randomized into two groups: the standard care group (n=40) and the intervention group (n=40). Both groups followed a 12-week program, with the intervention group performing additional eccentric and concentric exercises. Results: The intervention group showed greater improvements than the standard care group. Pain, measured by the Visual Analogue Scale (VAS), decreased from 7.30 ± 0.68 to 2.12 ± 0.56 in the intervention group, compared to a decrease from 7.02 ± 0.69 to 3.32 ± 0.65 in the standard care group. Grip strength increased by 13.37 kg in the intervention group (from 25.25 ± 2.39 to 38.62 ± 3.42 kg), while the standard care group saw an increase of 2.63 kg (from 24.79 ± 2.80 to 27.42 ± 3.13 kg). ROM in wrist flexion improved from 34.69 ± 2.43 to 59.47 ± 4.31 degrees in the intervention group, and from 32.93 ± 1.90 to 49.54 ± 3.50 degrees in the standard care group. Wrist extension ROM increased from 32.95 ± 1.94 to 53.19 ± 2.49 degrees in the intervention group, versus 30.66 ± 2.72 to 47.23 ± 3.52 degrees in the standard care group. EMG analysis revealed a significant reduction in EDC RMS amplitude in the intervention group from 575.53 ± 18.93 µV to 474.73 ± 22.70 µV.